These infinite threads - Mafi, Tahereh (London : Electric Monkey, 2023)
"The heir to the human throne, Kamran falls in love with Alizeh, heir to the Jinn throne, who fulfills a long-foretold prophecy as being destined to free her people, a discovery that causes Kamran to question everything he's been taught about the Jinn and their future in his kingdom"--
Keywords: Fantasy -- High Fantasy -- Persian Mythology